Asuhan Keperawatan Anak Pada Pasien Dengan Bronkopneumonia Di Ruang Rsud Prof. H. Muhammad Yamin, Sh Pariaman Tahun 2026 - Dara Febrina; Prima Yoselina; Reska Handayani; Erpita Yanti (CV. ITTC INDONESIA, 2026)
Bronchopneumonia is a respiratory tract infection characterized by the accumulation of secretions due to mucus buildup, which interferes with ventilation and increases the risk of impaired tissue oxygenation as well as complications such as respiratory failure. This study aims to describe the implementation of nursing care for children with bronchopneumonia, including assessment, nursing diagnoses, planning, implementation, and evaluation. The research method used is a case study of patient An. A who was treated in the Pediatric Ward of RSUD Prof. H. M. Yamin, SH Pariaman from March 3 to March 7, 2026. Data collection techniques included interviews, observation, physical examination, and documentation. The results showed that the patient experienced several nursing problems, namely ineffective airway clearance, ineffective breathing pattern, hyperthermia, and risk of nutritional deficit. Nursing interventions provided included airway management, respiratory monitoring, hyperthermia management, and nutritional management. After five days of nursing care, the patient’s condition improved, as indicated by more effective airway clearance, improved breathing pattern, normal body temperature, and increased appetite. It can be concluded that comprehensive and standard-based nursing care is effective in improving the patient’s condition. Nurses are expected to regularly monitor the patient’s respiratory status and provide education to the family regarding home care, including maintaining environmental hygiene, avoiding exposure to cigarette smoke, meeting nutritional needs, and conducting regular follow-up visits to prevent recurrence.